Macrophage Activation Syndrome and Renal Involvement: A Case Report - Rehman, Abaid ur; Taj, Sadia; Sabir, Omer; Said, Hafiz Usman; Tarif, Nauman (Pakistan Journal of Kidney Diseases, 2021)
Macrophage activation syndrome (MAS) is a severe, potentially fatal condition associated with excessive activation and expansion of macrophages and T cells (mainly CD8), leading to exaggerated inflammatory response. We describe here a case of MAS causing possibly ATN and review the literature.